Impact of mass migrations on the clonal variation of clinical Staphylococcus aureus strains isolated from the Western region of Saudi Arabia. Issue 3 (May 2019) - Al-Zahrani, Ibrahim A.; Azhar, Esam I.; Jiman-Fatani, Asif A.; Siddig, Loai A.; Yasir, Muhammad; Al-Ghamdi, Ahmed K.; Harwood, Colin R.
Abstract: Objectives: A rapid molecular typing system was used to determine the impact of mass migration on the clonal variation of Staphylococcus aureus isolates recovered from King Abdulaziz University Hospital (KAUH) Jeddah, in the western region of Saudi Arabia. This region experiences an annual influx of millions of pilgrims. Methods: Sma I-multiplex PCR typing (SMT) was used for the initial analysis of strains and the resulting data subsequently supported by Multi-Locus Sequence Typing (MLST). Results: A total of 89 S. aureus isolates were SMT typed and revealed a high degree of genetic variation, with 40 SMT profiles detected among the isolates. Representatives of all forty SMT types were subsequently analysed by MLST, identifying 26 sequence types. A novel sequence type (ST), named ST3303, was identified in two methicillin-sensitive S. aureus (MSSA) isolates. MSSA strains exhibited more diversity than methicillin-resistant S. aureus (MRSA) strains, with community acquired MSSA and MRSA strains reaching alarmingly high levels. Conclusion: The relatively high degree of genetic diversity found among S. aureus isolates of single hospital was attributed to the fact that Jeddah is the principal gateway to Mecca, visited each year by millions of pilgrims from many countries. The observed diversity clearly reflects the impact of such mass migrations in the rapid dissemination of strains world-wide. Our findings suggest the importance of surveillance programmes in locations affected by mass migrations, both to monitor their impact on endemic strains and for the detection of pandemic strains. SMT provides a cost-effective and sensitive typing method for achieving this objective.